البادهنج (فوهة الهواء) نظام تبريد البيوت في العصور الإسلامي ( دراسة تاريخية) (Journal of Humanitarian and Applied Sciences, 2023)
The fields of Islamic civilization varied: invention, discovery and development, and there is no place except for Muslim scholars to contribute, innovate, and know the nature of the desert and the temperature of the air. Muslim scholars did not prevent Muslim scholars from thinking about cooling air in homes and palaces, so they invented a machine called (Al.Bad-henj) that captures the outside air and passes it through Especially large cylinder into a tank made at the bottom of the machine, then distribute the air after it cools inside, to cool the air. This research explains this Islamic invention that spread in the Abbasid era, describing it and how to use it.